The coat protein p25 from maize chlorotic mottle virus involved in symptom development and systemic movement of tobacco mosaic virus hybrids - Zhang, Chao; Wang, Di; Li, Weimin; Zhang, Baolong; Abdel-Fattah Ouf, Gamal M.; Su, Xiaofeng; Li, Jun (Frontiers in Microbiology, 2022)
Viral coat protein (CP) has numerous critical functions in plant infection, but little is known about p25, the CP of maize chlorotic mottle virus (MCMV; Machlomovirus), which causes severe yield losses in maize worldwide. Here, we investigated the roles of p25 in pathogenicity and systemic movement, as well as potential interactions with host plants, using a hybrid tobacco mosaic virus (TMV)-based expression system. Highly conserved protein p25 is predicted to contain a membrane-anchored nuclear localization signal (NLS) sequence and an extracellular sequence. In transgenic Nicotiana benthamiana seedlings containing the movement protein (MP) of TMV (TMV-MP), p25 induced severe symptoms, including dwarf and foliar necrosis, and was detected in inoculated and non-inoculated leaves. After the deletion of NLS from nuclear-located p25, the protein was found throughout the host cell, and plant stunting and starch granule deformity were reduced. Systemic movement and pathogenicity were significantly impaired when the C-terminal regions of p25 were absent. Using virus-induced gene silencing (VIGS), the transcript level of heat shock protein HSP90 was distinctly lower in host plants in association with the absence of leaf necrosis induced by p25. Our results revealed crucial roles for MCMV p25 in viral pathogenicity, long-distance movement, and interactions with N. benthamiana.